PENGARUH ANTIBAKTERI SARI PATI DAUN SUNGKAI (Peronema canescens Jack) TERHADAP ZONA HAMBAT Shigella dysentriae - Dhede Faurizia; Linna Fitriani; Harmoko; Nopa Nopiyanti (Nusantara Hasana Journal, 2023)
Dysentery is an acute diarrheal disease with chronic symptoms, including diarrhea, fever, nausea, abdominal pain, and vomiting. Stool is liquid and mixed with blood that passes through the large intestine very quickly because bacteria have penetrated the large intestine caused by the bacterium Shigella dysentriae. Sungkai plant (Paronema canescens Jack) is one of the plants used as traditional medicine and contains antibacterial compounds consisting of phenolic compounds and their derivatives. This study aims to determine the effect of antibacterial activity of the extract of Sungkai Leaf Starch (Paronema canescens Jack) on the Inhibitory Zone of Shigella dysentriae. The research method is a laboratory experimental method, this type of research is a quantitative research, and the design used in the study is a Post Test Only Control Design. The results showed that sungkai leaf extract (Peronema canescens Jack) with concentrations of 65 grams, 75 grams, 85 grams, and 95 grams had different inhibitory effects on Shigella dysentriae. The conclusion from the non-parametric statistical test results using the Kruskal Wallis test, it was found that sig. < that is 0.001 < 0.05 which indicates that the resulting data has a significant difference.